Новые таксоны голубянок (Lepidoptera, Lycaenidae) из Закавказья и Средней Азии - Некрутенко, Ю.П. (Вестник зоологии, 1985)
Two lycaenid butterfly species and two subspecies are described as new. Lycaena melicertes sp. n.- from all representatives of the L. phoenicurus group differs by dark, ash-grey colour of the wing under side; type-locality: Araxes river valley near Negram, Nakhitshevan. Aricia scythissa sp. n. distinct by almost complete reduction of falces (as in A. teberdina Shelj.) along with characteristic sclerotization of the inner surface of valve (as in A. agestis [Den. et Schiff.]); type-locality: C. Tien-Shan Mts., Terskei-Alatau, Molo river valley, ca. 3200 m, Kirghizia. L. japhetica irghiza ssp. n. is described from Irghiz, Aktyubinsk distr., Kazakhstan, Polyommatus eroides erotulus ssp. n.- from Mistan, Talysh Mts., Zuvand, 2000 m, Azerbaijan.